Polarization-state-dependent attenuation and amplification in a columnar thin film. (26th October 2017) - Mackay, Tom G; Lakhtakia, Akhlesh
Abstract: We numerically investigated the plane-wave reflection-transmission characteristics of a columnar thin film (CTF) whose columns are made from a dissipative material but whose void regions are filled with an active material. By computing the reflectances and transmittances, we found that the CTF can simultaneously amplify s -polarized incident light and attenuate p -polarized incident light, or vice versa. This polarization-state-dependent attenuation and amplification phenomenon depends upon the angle of incidence and the thickness of the CTF.